AN INVESTIGATION INTO INTERNATIONAL STUDENTS’ EXPERIENCES STUDYING EAP IN A JOINT VENTURE UNIVERSITY IN CHINA - Lee, James (2014)
Globalisation is an inescapable aspect of the modern world. The number of large transnational corporations with a global presence has increased dramatically over the last two decades, particularly in developing nations (Roach, 2007). Such organisations spread their operations across regions in order to increase market share and profitability. Education is not excluded from this phenomenon. Traditionally internationalisation of Higher Education (HE) has involved student mobility. Students would travel from what Kachru (1985) refers to as Expanding Circle countries (such as China) to Inner Circle countries (such as the UK) in order to study in English. This remains an important trend; currently Chinese students constitute almost as many of the postgraduate students in the UK as native students, despite increased visa restrictions (The Guardian, 2014).